Impact of COVID-19 on nuclear medicine in the UK. Issue 2 (February 2021) - Dizdarevic, Sabina; Abdulla, Mahdi; Sewedy, Taha; Weston, Charlotte; Oxley, Caroline; Croasdale, Jilly; Redman, Stewart; Vinjamuri, Sobhan; Mayes, Christopher; Flux, Glen; Ward, Mike; Graham, Richard; et al.
Abstract : Purpose: COVID-19 brought about unprecedented challenges to healthcare, with nuclear medicine (NM) being no exception. The British Nuclear Medicine Society (BNMS) COVID-19 survey assessed the impact of the first wave of pandemic on NM services in the UK. With COVID-19 resurge compounded by seasonal winter pressures, we reflect and share lessons learnt from the first wave of pandemic to guide future strategy. Methods: A questionnaire consisting of 34 questions was sent out to all BNMS members over 2 weeks in May 2020, to evaluate the impact of 'lockdown'. Results: One hundred thirty-eight members (92 sites) from a multidisciplinary background responded. There was a 65% reduction across all services; 97.6% of respondents reported some reduction in diagnostic procedures and 71.3% reduction in therapies; 85% worked with a reduced workforce. The North East of England, Greater London and South East and Wessex were most affected by staff absences. The North East reported the highest number of COVID-19 positive staff; London reported the greatest lack of testing. The reported time required to clear the backlog was 1–12 months. Seventy-one percent of participants used BNMS COVID-19 guidance. Conclusion: The first wave caused a major disruption of NM service delivery and impacted on the workforce. The departmental strategies should tailor services to evolving local and regional differences in prevalence of COVID-19. A blanket shutdown of services with a 'one size fits all' strategy would likely have a severe impact on future delivery of NM and health services in general. Timely testing of staff and patients remains of paramount importance.